2017
DOI: 10.1016/j.jhep.2016.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid concentrations and fructose consumption are independently associated with NASH in children and adolescents

Abstract: Currently, it is not known whether dietary fructose consumption and uric acid (UA) concentration are linked with non-alcoholic steatohepatitis (NASH) in children and adolescents. Our aim was to test whether UA concentrations and fructose consumption are independently associated with NASH in children and adolescents with proven non-alcoholic fatty liver disease (NAFLD). We show that both dietary fructose consumption and serum UA concentrations are independently associated with NASH and fructose consumption was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
120
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(130 citation statements)
references
References 29 publications
3
120
0
7
Order By: Relevance
“…Other studies have shown that rats fed a fructose-rich diet have increased hepatic triglyceride and cholesterol levels [42], and fructose fed to rodents at supraphysiological doses induced steatosis and steatohepatitis by de novo lipogenesis [43]. Meta-analyses have also suggested that fructose consumption is related to the risk factors for metabolic syndrome, such as increased triglyceride levels, stimulated hepatic de novo lipogenesis, and increased visceral fat [44,45,46,47]. …”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that rats fed a fructose-rich diet have increased hepatic triglyceride and cholesterol levels [42], and fructose fed to rodents at supraphysiological doses induced steatosis and steatohepatitis by de novo lipogenesis [43]. Meta-analyses have also suggested that fructose consumption is related to the risk factors for metabolic syndrome, such as increased triglyceride levels, stimulated hepatic de novo lipogenesis, and increased visceral fat [44,45,46,47]. …”
Section: Discussionmentioning
confidence: 99%
“…In a study of adolescents, hyperuricemia independently predicted [OR 2.5 (1.87–2.83)] the presence of NASH after adjusting for age, sex and other components of the metabolic syndrome (51). Hyperuricemia in males has also been found to associate more strongly with NASH than simple steatosis and was significantly associated with hepatocyte ballooning, BMI, and younger age in multivariate analysis (128).…”
Section: Fructokinase the Principal Enzyme Driving Fructose-induced mentioning
confidence: 99%
“…A high intake of dietary fructose is associated with NAFLD and, in addition, it has been shown that children with NAFLD absorb and metabolize fructose more effectively than normal-weight children [33,34]. Several studies have shown that children and adults with NAFLD have a higher mean fructose intake mainly resulting from a higher consumption of soft drinks and fruit juices as compared with subjects of same age without NAFLD [35,36].…”
Section: Other Impact To Healthmentioning
confidence: 99%